Removal of lead and cobalt using silver nanoparticles immobilised titanium dioxide nanotubes / Nur Ain Najiha Abd Aziz and Norain Isa - Abd Aziz, Nur Ain Najiha; Isa, Norain (2020)
This study is conducted to synthesis the silver nanoparticle (AgNPs) and immobilization on titanium dioxide (TiO2) nanotubes. Evaluation of TiO2/AgNPs catalytic activity is performed to eliminate Co and Pb heavy metals. In order to achieve the objectives, several scopes need to be study .The preparation of AgNPs by salt reduction method. The reducing agent and metal precursor in this study are K. Breivifolia leaves and silver nitrate respectively. The factors that need to be consider are pH at 6, temperature where it is in a room temperature and the concentration of reducing agent and metal precursor. Preparation of silver nanoparticle (AgNPs) immobilized titanium dioxide (TiO2) nanotubes as a substrate by anodisation method. Ti wire will be used as anode and platinum electrode as cathode. The electrolyte for anodisation are 97 ml of ethylene glycol, 0.3 g of ammonium fluoride (NH4F) and 3 ml of 1.0 M potassium carbonate (K2CO3). The voltage which it is at 60V for 20 mins. Preparation of TiO2/AgNPs nanocatalyst was carried out by wet impregnation method. Furthermore, the characterization of the, TNTs, AgNPs and TNTs / AgNPs were done by using Field Emission Scanning Electron Microscopy (FESEM) and High-Resolution Transmission Electron Microscopy (HRTEM) and for lead and cobalt ion removal were analysing it by using Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES). Catalytic analysis was performed by using the TiO2/AgNPs nanocatalyst to extract lead and cobalt ions with different initial concentration which are 5, 10 and 15 ppm. The maximum removal for Pb is at concentration 10 ppm with time contact at 210 min. The maximum removal of Co is at concentration 10 ppm with time contact 210 mins.